STRATEGI PENGEMBANGAN USAHA SAYURAN KANGKUNG ORGANIK MENGGUNAKAN METODE ANALISIS SWOT - Achmad Syaichu (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
Abusiness shouldhave a mature planning and strategy.The right strategy certainly has a great influence in the development of the business itself.Thisresearchtried to examine the strategy of developingorganic vegetable business in POMOSDAusingSWOT analysis.The result of the research is based on the position in IE matrix, farmer group is in quadrant V. The core of strategy that can be applied by farmer group Gapoktan Japo is strategy of hold and maintain (Keeping and Maintain), through strategy of market penetration and product development. The results of SWOT analysis obtained a) S-O is maintain and improve service to consumers and expand distribution and marketing. b) W-O is a ensuring product certification and improving data archiving and exploiting opportunities. c) S-T is keepingand maintaining existing marketing areas. d) W-T is establishing cooperation (net working) with companies to look forword and obtain information market organic farming.